Management of side effects during and post‐treatment in breast cancer survivors. Issue 2 (27th August 2017) - Palesh, Oxana; Scheiber, Caroline; Kesler, Shelli; Mustian, Karen; Koopman, Cheryl; Schapira, Lidia
Abstract: Cancer‐related fatigue, insomnia, and cancer‐related cognitive impairment are commonly experienced symptoms that share psychological and physical manifestations. One or more of these symptoms will affect nearly all patients at some point during their course of treatment or survivorship. These side effects are burdensome and reduce patients' quality of life well beyond their cancer diagnosis and associated care treatments. Cancer‐related fatigue, insomnia, and cancer‐related cognitive impairment are likely to have multiple etiologies that make it difficult to identify the most effective method to manage them. In this review, we summarized the information on cancer‐related fatigue, insomnia, and cancer‐related cognitive impairment incidence and prevalence among breast cancer patients and survivors as well as recent research findings on pharmaceutical, psychological, and exercise interventions that have shown effectiveness in the treatment of these side effects. Our review revealed that most current pharmaceutical interventions tend to ameliorate symptoms only temporarily without addressing the underlying causes. Exercise and behavioral interventions are consistently more effective at managing chronic symptoms and possibly address an underlying etiology. Future research is needed to investigate effective interventions that can be delivered directly in clinic to a large portion of patients and survivors.